2015
DOI: 10.1016/j.jht.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting functional recovery after surgery and hand therapy in patients with Dupuytren's disease

Abstract: Study designProspective cohort study. IntroductionThe evidence of the relationship between functional recovery and impairment after surgery and hand therapy are inconsistent. Purpose of the studyTo explore factors that were most related to functional recovery as measured by DASH in patients with Dupuytren's disease. MethodsEighty-one patients undergoing surgery and hand therapy were consecutively recruited. ResultsThe three variables "need to take special precautions", "avoid using the hand in social context"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In other studies, 19% of patients were not able to return to their job following nerve repair and at least 3 months of hand therapy (Meiners et al., 2005), and 42% of patients reported problems with self-care following surgery and hand therapy for Dupuytren’s contracture (Engstrand et al., 2009). Two papers exploring patients’ recovery found that patients valued engagement in occupation as a more important outcome than improvements in objective measures (Cheung et al., 2016; Engstrand et al., 2015). In fact, including a focus on occupation in hand therapy was shown to improve client motivation and success (Astifidis et al., 2009; Bates and Mason, 2014; Jack and Estes, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In other studies, 19% of patients were not able to return to their job following nerve repair and at least 3 months of hand therapy (Meiners et al., 2005), and 42% of patients reported problems with self-care following surgery and hand therapy for Dupuytren’s contracture (Engstrand et al., 2009). Two papers exploring patients’ recovery found that patients valued engagement in occupation as a more important outcome than improvements in objective measures (Cheung et al., 2016; Engstrand et al., 2015). In fact, including a focus on occupation in hand therapy was shown to improve client motivation and success (Astifidis et al., 2009; Bates and Mason, 2014; Jack and Estes, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Dupuytren's disease (DD) is a common fibrotic disease confined to the hand that affects approximately 4% of the general UK and US populations [ 1 ]. The early stages of the disease are manifest as nodules that are typically quiescent for a period and then become active, progressing to cords and flexion deformities of the fingers in approximately 50% of patients [ 2 ] and result in loss of hand function [ 3 ]. Whilst the mainstay of treatment remains surgical excision (fasciectomy) of the diseased tissue or cords [ 4 ], approximately 40% of patients in the USA are treated by disruption of the cords using collagenase or needle fasciotomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review (Burley, Di Tommaso, Cox & Molineux, 2018) revealed that patients with hand injuries experienced occupational issues and found rehabilitation informed by an occupational perspective to be motivating (Bamford & Walker, 2010;Cheung, Clemson, O'Loughlin & Shuttleworth, 2016;Engstrand, Krevers & Kvist, 2015). Other themes from the scoping review included: the assumption that a bottom-up, biomechanical approach would improve occupational performance; a high focus placed on occupational outcome measures; and the use of informal discussion as an occupational strategy (Powell & Von Der Heyde, 2014;Weinstock-Zlotnick & Bear-Lehman, 2015).…”
Section: Introductionmentioning
confidence: 99%